2017
DOI: 10.5902/1980509828635
|View full text |Cite
|
Sign up to set email alerts
|

Fitossociologia Da Vegetação Arbórea Do Parque Nacional Do Iguaçu

Abstract: RESUMOFitossociologia da Vegetação Arbórea do Parque Nacional do Iguaçu -O Parque Nacional do Iguaçu está inserido no Bioma Mata Atlântica, sendo considerado o maior Parque extra-amazônico brasileiro. Apesar de sua importância e expressiva área de superfície florestal, poucos são os estudos científicos relacionados à sua vegetação. Com o objetivo de atender esta demanda foi realizado inventário fitossociológico da vegetação arbórea por meio de parcelas instaladas em diferentes condições ambientais, buscando a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
2
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 8 publications
0
13
2
6
Order By: Relevance
“…Both specimens were collected at the Parque Nacional do Iguaçu, the largest remnant of the Brazilian Atlantic Forest that once covered the region (e.g. Paviolo et al, 2016), in areas of Seasonal Semidecidual Forest (see Souza et al, 2017). We were able to find photos on the iNaturalist database (one from Misiones, Argentina and other from the region of Curitiba, Paraná, Brazil), that Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…Both specimens were collected at the Parque Nacional do Iguaçu, the largest remnant of the Brazilian Atlantic Forest that once covered the region (e.g. Paviolo et al, 2016), in areas of Seasonal Semidecidual Forest (see Souza et al, 2017). We were able to find photos on the iNaturalist database (one from Misiones, Argentina and other from the region of Curitiba, Paraná, Brazil), that Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…In the right portion of the diagram, associated with the highest altitude and low fertility soils with high aluminum content, the characteristics of the Ecotone MOF/SSF environment in the PNI (Souza et al, 2017), were positioned the preferential species of ombrophylous forests A. angustifolia and I. paraguariensis (Saueressig, 2012). Reissmann et al (1999) identified I. paraguariensis occurring naturally also in acidic soils with high aluminum content.…”
Section: Discussionmentioning
confidence: 99%
“…Salamuni et al (2002) pointed out that this National Park presents two geomorphological compartments: (I) the Central and North region formed by a more rugged relief, locally steep relief, characterizing more elongated and carved interfluves with undulated hills to strongly undulated; (II) the southern region, formed by gently rolling to rolling hills, with predominance of tabular forms that, strictly speaking, are a constant in the Paraná basaltic spills. Souza et al (2017) have identified in the Park Eutrophic MELANIC Tb GLEISSOLO, Eutrophic REGOLITIC NEOSOLS, Dystrophic RED LATOSOL, Eutrophic RED LATOSOL and Eutrophic RED NITOSOL; the last two with the greatest recurrence. Bhering (2007) reported, in addition, the occurrence of ORTHIC RENDZIC CHERNOSOL, HAPLIC GLEISSOL and Eutrophic LITOLIC NEOSOL.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Forests in the INP are composed of different vegetation formations. Alluvial, Submontane and Montane formations of Semi-deciduous Forest (FES) predominate in the south and central regions and, in the north region, an ecotone between FES and Ombrophillous Mixed Forest (FOM), as well as Alluvial FOM are observed (Souza et al, 2017).…”
Section: Methodsmentioning
confidence: 99%